2021
DOI: 10.3390/molecules26061653
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity Evaluation of Coumarin-3-Carboxamide Derivatives

Abstract: A series of novel coumarin-3-carboxamide derivatives were designed and synthesized to evaluate their biological activities. The compounds showed little to no activity against gram-positive and gram-negative bacteria but specifically showed potential to inhibit the growth of cancer cells. In particular, among the tested compounds, 4-fluoro and 2,5-difluoro benzamide derivatives (14b and 14e, respectively) were found to be the most potent derivatives against HepG2 cancer cell lines (IC50 = 2.62–4.85 μM) and HeLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Their chemical versatility has additionally enabled the synthesis of a large variety of functionalized skeletons. Modes of action are variable, yet potent [77][78][79][80]. Inhibition of cell wall synthesis, permeabilization and disintegration of bacterial peripheral layers, restriction of bacterial physiology, oxygen uptake and oxidative phosphorylation, efflux pump inhibition, modulation of antibiotic susceptibility, biofilm inhibition, hindrance of the microbial protein adhesion to the host's polysaccharide receptors, and attenuation of bacterial virulence, are known and acclaimed mechanisms of action of such elements [67,69,70,81].…”
Section: Plant-derived Biomoleculesmentioning
confidence: 99%
“…Their chemical versatility has additionally enabled the synthesis of a large variety of functionalized skeletons. Modes of action are variable, yet potent [77][78][79][80]. Inhibition of cell wall synthesis, permeabilization and disintegration of bacterial peripheral layers, restriction of bacterial physiology, oxygen uptake and oxidative phosphorylation, efflux pump inhibition, modulation of antibiotic susceptibility, biofilm inhibition, hindrance of the microbial protein adhesion to the host's polysaccharide receptors, and attenuation of bacterial virulence, are known and acclaimed mechanisms of action of such elements [67,69,70,81].…”
Section: Plant-derived Biomoleculesmentioning
confidence: 99%
“…In ddition to, their potent activity against human fungal pathogens such as C. tropicalis, C. albicans, and Aspergillus fumigatus. [18][19][20] Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities. [20][21][22][23][24][25] Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti-inflammatory [26][27][28][29][30] besides their significant with various fungicidal activities .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities. [20][21][22][23][24][25] Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti-inflammatory [26][27][28][29][30] besides their significant with various fungicidal activities . [31,32] In addition, many scientific reported have also demonstrated that the sulfonamide moiety itself possess interesting pharmacological activities and therapeutic functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticancer activities for coumarins have been also reported. Coumarin-3-carboxamide derivatives have been reported, and 4-fluoro and 2,5-difluoro benzamides presented activities against HepG2 and HeLa cancer cell lines comparable to doxorubicin, exhibiting low cytotoxicity against LLC-MK2 normal cell line [12]. From the combination of simple coumarins (osthole, umbelliferone, esculin or 4-hydroxycoumarin) with sorafenib, an antiglioma compound was also reported by studying human glioblastoma multiforme (T98G) and anaplastic astrocytoma (MOGGCCM) cells lines [13].…”
mentioning
confidence: 99%